Parenteral nutrition effects of Omega-3 fatty acids on C-reactive protein, high-density lipoprotein, lymphocyte characteristics and the treatment of critically ill patients - Ni, Chunhua; Cao, Jianxun; Li, Dechuan; Wu, Wei; Cao, Lei; Zhu, Chaoyun (Cellular and Molecular Biology, 2020)
To study the effects of omega-3 fatty acid parenteral nutrition on the nutrition, inflammatory responses, immunity and prognoses of critically ill cancer patients. A total of 80 critically ill cancer patients were randomly divided into an observation group and a control group, 40 cases in each group. Both groups of patients received equal-nitrogen and equal-calorie enteral and parenteral nutrition. The observation group, on this basis, was added with omega-3 fatty acid parenteral nutrition. The weekly nutritional status measures, inflammatory response measures, immune function measures and prognosis measures (ICU mortality, ICU stay, infectious complications) of the two groups were observed. The nutrition, inflammatory response and immune measures of the observation group were improved compared with the control group. The ICU stay in the observation group was shorter than the control group. Compared with the control group, the ICU mortality rate and infectious complication rate were lower in the observation group, but the differences were not significant (P mortality = 0.13, P infection rate = 0.165). Omega-3 fatty acid parenteral nutrition could improve patients' nutritional status and immune function, reduce the body's inflammatory responses and shorten the length of hospital stay, but couldn't significantly improve ICU mortality and reduce the incidence of infectious complications.